2023
DOI: 10.1186/s13049-023-01168-9
|View full text |Cite|
|
Sign up to set email alerts
|

Trauma patient transport to hospital using helicopter emergency medical services or road ambulance in Sweden: a comparison of survival and prehospital time intervals

Oscar Lapidus,
Rebecka Rubenson Wahlin,
Denise Bäckström

Abstract: Background The benefits of helicopter emergency medical services (HEMS) transport of adults following major trauma have been examined with mixed results, with some studies reporting a survival benefit compared to regular emergency medical services (EMS). The benefit of HEMS in the context of the Swedish trauma system remains unclear. Aim To investigate differences in survival and prehospital time intervals for trauma patients in Sweden transported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…After publication of this article [ 1 ], the authors reported that in Fig. 3 the text along the y-axis is incorrect; the figure should have appeared as shown below.…”
mentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that in Fig. 3 the text along the y-axis is incorrect; the figure should have appeared as shown below.…”
mentioning
confidence: 99%